2015
DOI: 10.1270/jsbbs.65.127
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the black gram [<i>Vigna mungo</i> (L.) Hepper] gene pool as revealed by SSR markers

Abstract: In this study, 520 cultivated and 14 wild accessions of black gram (Vigna mungo (L.) Hepper) were assessed for diversity using 22 SSR markers. Totally, 199 alleles were detected with a mean of 9.05 alleles per locus. Wild black gram showed higher gene diversity than cultivated black gram. Gene diversity of cultivated accessions among regions was comparable, while allelic richness of South Asia was higher than that of other regions. 78.67% of the wild gene diversity presented in cultivated accessions, indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 33 publications
1
44
2
Order By: Relevance
“…However, none of the QTLs for seed dormancy were common among these four Vigna species. In fact, we expected that black gram shares some common QTLs for pod indehiscence and seed dormancy with mungbean because the two species both originated and are domesticated in India and show very similar morphological characteristics and are cultivated and used in the same fashion ( Tomooka et al, 2002 ; Kaewwongwal et al, 2015 ). However, the results indicated that different mechanisms control seed dormancy in these five Vigna species.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the QTLs for seed dormancy were common among these four Vigna species. In fact, we expected that black gram shares some common QTLs for pod indehiscence and seed dormancy with mungbean because the two species both originated and are domesticated in India and show very similar morphological characteristics and are cultivated and used in the same fashion ( Tomooka et al, 2002 ; Kaewwongwal et al, 2015 ). However, the results indicated that different mechanisms control seed dormancy in these five Vigna species.…”
Section: Discussionmentioning
confidence: 99%
“…Because they are stable, fast, multiā€allelic, and require less DNA, SSR molecular markers have been extensively used for genetic diversity, quantitative trait loci, and association analyses in black gram [ Vigna mungo (L.) Hepper], maize ( Zea mays L.), rice ( Oryza sativa L.), and tobacco (Obara et al, 2010; Yang et al, 2013; Zhang et al, 2014; Kaewwongwal et al, 2015). Dai et al (2015) analyzed the genetic diversity of 33 tobacco resistant backbone parents based on 103 SSR markers and obtained a PIC value of 0.343.…”
Section: Discussionmentioning
confidence: 99%
“…Vigna mungo (L.) Hepper or black gram is a diploid plant with 2 n = 2 x = 22 chromosomes. It belongs to the family Leguminosae, subfamily Papilionoideae, clade Millettioid [ 1 ], and is a tropical legume crop species that is cultivated in Asia, Africa, and America [ 2 ]. Black gram is an economically important Vigna species, which provides high-protein food [ 3 ].…”
Section: Introductionmentioning
confidence: 99%